CLINICAL AND EPIDEMIOLOGICAL FACTORS DETERMINING PROPAGATION AND CLINIC OF UROGENITAL TRICHOMONIASIS IN WOMEN - K. S. Akyshbayeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
The problem of urogenital trichomoniasis (UGT) is relevant not only due to its high prevalence and multiple organ lesions, but also to the ability to have a negative impact on reproductive health. In Kazakhstan, UGT is one of the leading infections in the structure of sexually transmitted infections: in 2011 51.5%; 2012 — 43.5%; 2013 — 42.0% with the prevalence of co-infection with other STIs, in which the rate of complications is increased by 2 times and are more profound with the involvement of inflammation in the upper urogenital tract. The recorded incidence of trichomoniasis in the RK is characterized by annual rate decrease (since 2011 a 1.5 times decrease) due to small fluctuations of syphilis, gonorrhea, chlamydia morbidity which indicates a large reservoir of latent infection, and low level of diagnostics. Most clearly demonstrates this situation an incidence of UGT in 2 cities: so in Astana in 2013, the recorded incidence decreased by 2.8 times compared to 2011; in Almaty — 6 times in 2012 and 4.3 times in 2013. Conducted clinical and epidemiological analysis of UGT morbidity in women allowed to identify the following: in recent years the tendency of UGT to growth with a significant proportion of latent asymptomatic forms (for more than one quarter of patients with UGT, UGT is most common in young adults, average age 30.5±2.5 years); in half of the cases recorded, mixed trichomonas infection, mostly in combination with Chlamydia, which causes a high incidence of complications of the upper urogenital tract; there is a high frequency of trichomonas infection combination with infections caused by Candida, mycoplasma, which determines the prospects of the combination therapy UGT in combination with drugs, correcting immunodeficiency. There is quite a high incidence of gynecological pathology, the severity of which depends on the frequency of the spectrum of pathogens that are associated with T. vaginalis. The data obtained allows to select women with trichomonas infection of the urogenital tract with the complication risk that affect the reproductive function; UGT develops together with urogenital tract disbacteriosis with a predominance of Staphylococcus species, having adhesive, lizotsimogenic, hemolytic activity that must be considered when conducting a combined therapy with drugs, correcting microflora. The frequency of various complications was significantly higher in patients with mixed infection. Particular attention is drawn to the attention of the high frequency of adnexitis, uterine fibroids, their rate was equivalent to and higher than the corresponding figures of 1.9 times and 5 times, respectively (38.0% versus 20.0% and 7.8%, p < 0,05) at monoinfection. In this group of ovarian cyst recorded in 10.1% of cases. Basically, the above-mentioned diseases were observed in patients with trichomonas, chlamydial infection. Adnexitis and uterine fibroids in all 30 cases were recorded in patients co-infected with this that has made 75,0±6,8%. Our findings are consistent with studies of high risk of pelvic inflammatory disease in women with trichomoniasis. Other studies have reported increases of 1.9 times the risk of tubal infertility in women with trichomoniasis. Trichomoniasis can also play a role in cervical neoplasia and postoperative infections.